1995
DOI: 10.1002/star.19950471003
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Maize Starch Gels Selectively Regulated by the Addition of Hydrocolloids

Abstract: 378 starch/stiirke 47 (1995) Nr 10. S . 378-384 0 VCH Ve rlagsgeaellschat't mbH, D-69451 Weinheim, 1995 0038-9056/95/1010-0378$05.00+.25/0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 7 publications
7
70
2
Order By: Relevance
“…This is attributable to increased water retention and better water distribution which affects the crumb hardness (ARMERO; COLLAR, 1996;EIDAM et al, 1995). Figure 3 shows the hardness increase of the crumb during the bread storage at 25 °C.…”
Section: Effect Of Bg On the Crumb Staling During Storagementioning
confidence: 99%
See 1 more Smart Citation
“…This is attributable to increased water retention and better water distribution which affects the crumb hardness (ARMERO; COLLAR, 1996;EIDAM et al, 1995). Figure 3 shows the hardness increase of the crumb during the bread storage at 25 °C.…”
Section: Effect Of Bg On the Crumb Staling During Storagementioning
confidence: 99%
“…It seems that the effect of gums results from two opposite phenomena: firstly, due to an increase in the rigidity as a consequence of the decrease in the swelling of the starch granules and the amylose lixiviation; secondly, due to a weakening effect on the starch structure caused by inhibition of the amylase chain association (BILIADERIS et al, 1997). Other authors (ARMERO;COLLAR, 1996;EIDAM et al, 1995) proposed that hydrocolloids have a weakening effect on the starch structure that promotes better water distribution and retention and a decrease in the crumb resistance. He and Hoseney (1990) proposed that the decrease in moisture content favors the rapid formation of cross-links between starch molecules and proteins, yielding a faster hardening of the bread and, as a consequence, if the hydrocolloids can act in favor of the retention of water in the crumb structure, there will be less hardening.…”
Section: Effect Of Bg On the Crumb Staling During Storagementioning
confidence: 99%
“…As far as the rheology of cross-linked waxy maize starch is concerned, Genovese & Rao (2003) showed that the exchange of the continuous phases of cross-linked waxy maize and tapioca (19.3% amylose content) starch pastes did not influence the overall suspension rheology. Mixing other polysaccharides with starch is performed to modify paste flow properties leading to desired specific textures for food applications (Eidam, Kulicke, Kuhn, & Stute, 1995;Savary, Handschin, Conde-Petit, Cayot, & Doublier, 2008;Tecante & Doublier, 1999) or to enhance film forming properties (Lafargue, Lourdin, & Doublier, 2007). If starch components are released into suspension continuous phase, interaction between this compound and other hydrocolloids present may become critical.…”
Section: Introductionmentioning
confidence: 99%
“…The food additives like various stabilizers and emulsifiers may be used in its manufacturing to enhance shelf stability and improve texture along with softness. On other hand, because of various hydrocolloids on wheat flour starch synergistic interaction occurs and the intensity of the reaction is depending upon the nature and quantity of the gum being used as hydrocolloid (Eidam et al, 1995). There are various uses of hydrocolloids in many of foods and these serve as thickening, gelling and stabilizing agents.…”
Section: Introductionmentioning
confidence: 99%